IMPLEMENTASI MBKM MAGANG MANDIRI BALAI BAHASA SUMSEL 2025 - Anisa; Labiibah Aulia; Intan Muhpina Damayanti; Chandra Wardana; Putri Oktarina; Mutiara Dewi Mavinka; Zaskya Salbila; Anisa Sahid; Husni Nurazizah; Vivi Suci Meilindra; Dwi Siti Aisyah; Septian Rizki Ananda; Desi Irliani; Irni Yuniana; Izza Vella Qhonita; Vica Andinie; Achmad Wahidy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Independent Internship Program under the Merdeka Belajar Kampus Merdeka (MBKM) initiative is designed to provide students with relevant learning experiences through direct involvement in the professional work environment. One of the issues identified in language and literature is the low interest of children in reading materials based on local culture and the limited use of language and literature products by students and the community. This initiative aims to enhance language knowledge, strengthen the use of regional languages, and optimize language services by involving students in various activities related to language and literature. Its implementation uses a participatory methodology supported by qualitative descriptive techniques. Students play a role in four main aspects: literacy, revitalization of regional languages, translation, and digital-based language services. The results of the activities showed an increased interest of children in reading local folklore stories, improved language knowledge among students, enhancement of the quality of bilingual children's story manuscripts, and optimization of language content dissemination through digital media. These findings indicate that experiential learning through the MBKM Program is effective in supporting the improvement of literacy, the preservation of local languages, and the development of students' language competencies in a contextual and sustainable manner.